Are Raw Brassica Vegetables Healthier Than Cooked Ones? A Randomized, Controlled Crossover Intervention Trial on the Health-Promoting Potential of Ethiopian Kale - Schlotz, Nina; Odongo, Grace A.; Herz, Corinna; Waßmer, Hanna; Kühn, Carla; Hanschen, Franziska S.; Neugart, Susanne; Binder, Nadine; Ngwene, Benard; Schreiner, Monika; Rohn, Sascha; Lamy, Evelyn (Nutrients, 2018)
The present human intervention trial investigated the health-promoting potential of B. carinata, with a focus on effects of thermal processing on bioactivity. Twenty-two healthy subjects consumed a B. carinata preparation from raw (allyl isothiocyanate-containing) or cooked (no allyl isothiocyanate) leaves for five days in a randomized crossover design. Peripheral blood mononuclear cells were exposed to aflatoxin B1 (AFB1), with or without metabolic activation using human S9 mix, and subsequently analyzed for DNA damage using the comet assay. Plasma was analyzed for total antioxidant capacity and prostaglandin E2 (PGE2) levels. Cooked B. carinata significantly reduced DNA damage induced by AFB1 as compared to baseline levels (+S9 mix: 35%, −S9 mix: 33%, p ≤ 0.01, respectively). Raw B. carinata only reduced DNA damage by S9-activated AFB1 by 21% (p = 0.08). PGE2 plasma levels were significantly reduced in subjects after consuming raw B. carinata. No changes in plasma antioxidant capacity were detectable. A balanced diet, including raw and cooked Brassica vegetables, might be suited to fully exploit the health-promoting potential. These results also advocate the promotion of B. carinata cultivation in Eastern Africa as a measure to combat effects of unavoidable aflatoxin exposure.